1999
DOI: 10.1023/a:1018759201290
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examines the predictors of mental health service use among patients in an ethnically diverse public-care women's clinic. While waiting for their clinic appointments, 187 Latina, African American, and White women were interviewed about their attitudes towards mental illness and mental health services. White women were much more likely to have made a mental health visit in the past than the ethnic minority women. Having a substance use problem, use of mental health services by family or friends, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(90 citation statements)
references
References 24 publications
4
79
2
Order By: Relevance
“…These findings include that mentally ill individuals are inferior and should be isolated from others (Silva de Crane and Spielberger 1981) and that mentally ill individuals are more dangerous than non-mentally ill individuals (Whaley 1997). In contrast to these findings, Alvidrez (1999) found that Latino women were less likely to endorse beliefs that mental illness carries a stigma than African American and white non-Latino women. However, Alvidrez explains that this result may have been confounded by the lack of variability in the responses across the three groups.…”
Section: Cultural Influences In Meaning and Expressioncontrasting
confidence: 86%
“…These findings include that mentally ill individuals are inferior and should be isolated from others (Silva de Crane and Spielberger 1981) and that mentally ill individuals are more dangerous than non-mentally ill individuals (Whaley 1997). In contrast to these findings, Alvidrez (1999) found that Latino women were less likely to endorse beliefs that mental illness carries a stigma than African American and white non-Latino women. However, Alvidrez explains that this result may have been confounded by the lack of variability in the responses across the three groups.…”
Section: Cultural Influences In Meaning and Expressioncontrasting
confidence: 86%
“…It may also be the case that individuals suffering from mental disorder experience discrimination related to mental illness as well as race which is not captured here, but influences the help-seeking decisions of blacks differently than whites. Indeed, stigma around mental health issues has been found to influence help-seeking in general (Conner et al 2010;Rüsch et al 2009) and among African Americans more specifically (Alvidrez 1999;Snowden 2001;Conner et al 2010). The relationship between stigmatization, discrimination related to mental illness, and how they may interact with other forms of discrimination is an area in need of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Persons belonging to racial and ethnic minority groups, in particular, underutilize mental health services. Compared to whites, for example, African Americans have been found to be less likely to use outpatient mental health services (Wang et al 2005a, b;Alvidrez 1999; Barrio et al 2003;Padgett et al 1994;U.S. Department of Health and Human Services 2001;Snowden 2001), to fill antidepressant prescriptions (Satre et al 2010), and to spend less on psychotherapy (Chen and Rizzo 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, Blacks tend to hold more stigmatizing perceptions of mentally ill individuals than Whites do (Anglin et al 2006;Pescosolido et al 1999;Whaley 1997;Corrigan and Watson 2007). With respect to service use, Blacks report that stigma is a significant treatment barrier in qualitative studies (Alvidrez et al 2005;Cooper-Patrick et al 1997;Keating and Robertson 2004;Thompson et al 2004), and some quantitative studies have found that stigma-related beliefs account, at least in part, for ethnic disparities in mental health services use (Alvidrez 1999;Ojeda and McGuire 2006).…”
Section: Introductionmentioning
confidence: 99%